Relationship Between Sarcopenia, Obesity, Osteoporosis, and Cardiometabolic Health Conditions and Physical Activity Levels in Korean Older Adults - Park, Hun-Young; Jung, Won-Sang; Kim, Sung-Woo; Lim, Kiwon (Frontiers in Physiology, 2021)
This study aimed to analyze the status of sarcopenia, obesity, osteoporosis, and cardiometabolic disease according to the level of physical activity (PA) among elderly people in Korea. Among the data obtained from the National Health and Nutrition Survey (2008–2011), we analyzed the data of a total of 3,573 Korean elderly people over 65 years of age who were surveyed for dual X-ray absorptiometry (DXA) and PA. Higher levels of PA were associated with a lower prevalence of cardiometabolic disease (χ2 = 33.865, p <0.001), osteoporosis (χ2 = 94.198, p <0.001), sarcopenia, obesity, and sarcopenic obesity (χ2 = 71.828, p <0.001). Above moderate-active PA was associated with lower body weight (p <.001), body fat mass (p <.001), and percent body fat (p <.001), and higher free-fat mass (p <.001) and appendicular skeletal muscle mass (ASM) (p <.001) than in low-active PA. In addition, when high-active is the risk factors of cardiometabolic were lower in waist circumference (p =.001), total cholesterol (TC) (p =.015), and triglyceride (TG) (p <.001) than low- and moderate-active PA, and higher in high-density lipoprotein cholesterol (HDL-C) (p <.001). The prevalence of cardiometabolic diseases was significantly decreased in high-active PA (odds ratio (OR) 0.60, 95% confidence interval (CI) 0.50–0.71); waist circumference (OR 0.85 95% CI 0.73–0.99; OR 0.59 95% CI 0.50–0.70) and HDL-C (OR 0.76 95% CI 0.65–0.88; OR 0.56 95% CI 0.47–0.67) significantly improved in moderate- and high-active PA, respectively, and TG (0.67 95% CI 0.55–0.80) significantly improved in high-active PA. Osteoporosis (OR 0.62, 95% CI 0.53–0.74; OR 0.46, 95% CI 0.38–0.55) and sarcopenia (OR 0.77, 95% CI 0.60–0.98; OR 0.73, 95% CI 0.57–0.93) were significantly improved in moderate- and high-active PA, respectively. The incidence of obesity (OR 0.47, 95% CI 0.39–0.57) and sarcopenic obesity (OR 0.47, 95% CI 0.30–0.75) were significantly decreased in high-active PA. Therefore, we verified a lower prevalence of sarcopenia, osteoporosis, obesity, and cardiac metabolic disease in Korean elderly with more active PA. This suggests that more active PA maybe reduce the prevalence of sarcopenia, osteoporosis, obesity, and cardiometabolic diseases in older adults.